Expression Profile and Potential Function of Circular RNAs in Peripheral Blood Mononuclear Cells in Male Patients With Primary Gout - Fei Dai; Fei Dai; Quan-Bo Zhang; Quan-Bo Zhang; Yi-Ping Tang; Yi-Ping Tang; Yi-Xi He; Yi-Xi He; Ting Yi; Ting Yi; Yu-Feng Qing; Yu-Feng Qing (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) are non-coding RNAs (ncRNAs) with a single-stranded covalently closed-loop structure, and their abnormal expression may participate in the pathogenesis of various human diseases. Currently, knowledge of circRNAs in gout is limited. In this case-control study, human circRNA microarrays were used to identify differentially expressed circRNAs in peripheral blood mononuclear cells (PBMCs) from patients with primary gout (n = 5) and healthy controls (HC; n = 3). Bioinformatics methods were used to analyze significantly different circRNAs (fold change >1.5, p < 0.05). In addition, four significantly differentially expressed circRNAs were selected for quantitative real-time polymerase chain reaction to detect expression levels in 90 gout patients and 60 HC. Subsequently, circRNA-miRNA-mRNA network was established to predict the function of circRNAs of interest. Microarray analysis indicated that 238 circRNAs were upregulated and 41 circRNAs were down-regulated in the gout group (fold change >1.5, p < 0.05). Bioinformatics analysis showed that differentially expressed circRNAs were involved in the pathogenesis of gout via various pathways. Moreover, the expression levels of hsa_circRNA_103657 and hsa_circRNA_000241 were significantly higher in the gout group than those in the HC group, and both correlated significantly with lipid metabolism parameters. Furthermore, the area under the curve of hsa_circRNA_103657 was 0.801 (95% confidence interval (CI): 0.730–0.871; p < 0.001). Our results provide novel insights into the pathogenesis of primary gout. Differentially expressed circRNAs were identified in the PBMCs of gout patients, and these differential circRNAs may play important roles in the development and progression of gout.